Daydreams and Reflections on Black Theater, Cultural Politics, and the Anti-Racist Struggle with Hilton Cobra (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
In May 2024, actor Hilton Cobra gave this interview about his monologue, Bring me the head of Lima Barreto. The play his is a celebration of the actor's 40th anniversary. A hallmark of his work is the fight against racism and the promotion of theater as an anti-racist epistemic tool. In the interview he discusses the main motivations for creating the play, his work as an actor and the partnership between Onisajé (Fernanda Julia) and Luiz Marfuz. In addition to reflecting on Brazilian black theater and the Brazilian cultural scene post-covid-19.
Keywords: black theater; Hilton Cobra; black body; cultural politics